New Crustal Vs Model Along an Array in South‐East China: Seismic Characters and Paleo‐Tethys Continental Amalgamation - Tingzi Li; Liang Zhao; Bo Wan; Zheng‐Xiang Li; Thomas Bodin; Kun Wang; Huaiyu Yuan (Geochemistry, Geophysics, Geosystems, 2020)
Abstract The assembly of East Asia was closely linked to the closure of the Tethyan oceans. In south‐east China, the closure of the Paleo‐Tethys ocean led to a continental collision between the South China and North China blocks (SCB and NCB), forming the world renowned (ultra‐) high pressure (UHP) metamorphic belt of the Dabie‐Sulu Orogen. The region was subsequently reworked by postorogenic extensional processes. These tectonic processes likely have left lithospheric scars identifiable by seismic imaging techniques. Here we characterize seismic structures across the orogen and analyze processes related to the closure of the Paleo‐Tethys. Using cutting‐edge tomographic approaches and ambient noise dispersion data, we developed a fine‐scale crustal shear‐wave velocity model beneath key crustal domains in the region. Distinct crustal scale velocity domains are identified, corresponding to the normal Precambrian crust, slow‐velocity suture zones and fault systems, and fast‐velocity orogens, suggesting a deep root of the corresponding surface geological features. By combining recent models of active‐source, gravity and magnetotellurics, characteristic lithospheric deformation patterns such as crustal thrust systems and lithospheric wedges can be inferred, which are attributed to a northward subduction of the SCB lithosphere and the eventual continental collision after the closure of the Paleo‐Tethys Ocean.